Efeito da desfolha e do armazenamento de cachos em câmara fria antes do esmagamento em uvas e vinhos Chardonnay e Cabernet Sauvignon da região da Campanha, RS. - Potter, Gabriela Hermann (2009)
The Brazilian wines have been improving in the last few years, mainly because: the utilization of better adapted varieties of Vitis vinifera grapes, the expansion to new and different areas for grapes, to better vineyard practices and the use of good and sound enologic techniques. There are practices on vineyard e after harvest that could help to improving the wine quality. The defoliation is an example. This practice consist of taking off the leaves nearby the clusters facing the east side of the vineyard, to promote better illumination and ventilation for the fruit, all aiming to improve grape quality. The use of cold temperature storage of grapes before the crushing is also a common technique which improves the control about the fermentation process and helps to reduce the logistic problems. The aim of this work was to evaluate the effect of partial defoliation on physical-chemistry parameters of Cabernet Sauvignon grapes and wines, and also to evaluate the effect in wines from Cabernet Sauvignon and Chardonnay grapes, kept in cold storage temperatures, produced on the southwest of the state of Rio Grande do Sul, Brazil. The grapes were harvested in 2008, from a commercial vineyard growning in the trellis system. The defoliation intensity was 20% and was done only on the side of the vineyard that receives sun in the morning and when the berry was in the pea-size. After the harvest, half of the grapes was immediatelly crushed and fermented, called Standard , and the other half was stored for four days at 10ºC before crushing and fermentation, called Cold . The musts were fermented in small lots, in triplicate, with temperature control, staying on the skins for eight days in the case of red wines. The majority of the physical-chemistry analyses was done according Ribéreau-Gayon et al. (1976) and Amerine & Ough (1986). Total phenolics was made by the Folin Ciocalteau Method, according Singlenton & Rossi (1965). The defoliation made in Cabernet Sauvignon showed higher values of total phenolic content for grapes (1.073 against 1.283mg EAG.100g-1 fresh skin) and anthocyanins (304 against 410mg malvidin.100g-1 fresh skin). Consequently, the wines from grapes with defoliation result in more color, more anthocyanins (290 against 301mg malvidin.L-1) and more total phenolic (2.564 against 2.951mgEAG.L-1). On the chilled grapes, the treatment Cold had higher values of anthocyanins and phenolic contents on Cabernet Sauvignon grapes and lower values of pH on white and red wines. On the sensory analyses of wines using Paired Comparison Test, althought the majority of the judges had preferred the samples from the treatments with defoliation and Cold , statistically this results are not significant. The conclusion is that the use of partial defoliation and of cold temperature for clusters storage before the crushing and fermentation, might improve wine quality at least in the condition of this work.